Meningitis and a safe dexamethasone-eluting intracochlear electrode array. (July 2015) - Stathopoulos, Dimitra; Chambers, Scott; Adams, Louise; Robins-Browne, Roy; Miller, Christopher; Enke, Ya Lang; Wei, Benjamin P C; O'Leary, Stephen; Cowan, Robert; Newbold, Carrie
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives To evaluate the potential risk of pneumococcal meningitis associated with the use of a dexamethasone-eluting intracochlear electrode array as compared with a control array. Methods In two phases, adult Hooded–Wistar rats were implanted via the middle ear with an intracochlear array and were inoculated with Streptococcus pneumoniae 5 days post-surgery. Phase I created a dosing curve by implanting five groups (n = 6) with a control array, then inoculating 5 days later with different numbers of S. pneumoniae: 0 CFU, 103 CFU, 104 CFU, 104 CFU repeated, or 105 CFU (colony forming units). A target infection rate of 20% was aimed for and 104 CFU was the closest to this target with 33% infection rate. In phase II, we implanted two groups (n = 10), one with a dexamethasone-eluting array, the other a control array, and both groups were inoculated with 104 CFU of S. pneumoniae 5 days post-surgery. Results The dexamethasone-eluting array group had a 40% infection rate; the control array group had a 60% infection rate. This difference was not statistically significant with a P value of ≥0.5. Conclusion The use of a dexamethasone-eluting intracochlear electrode array did not increase the risk of meningitis in rats when inoculated with S. pneumoniae via the middle ear 5 days following implantation.